Pengaruh Kebosanan Kerja Terhadap Perilaku Cyberloafing Dengan Stres Kerja Sebagai Variabel Mediasi Pada Karyawan Generasi Milenial - Riski Ayuningtyas; Rosaly Fransiska (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The phenomenon that has occurred lately is that the millennial generation gets bored faster than other generations. The purpose of this study was to examine the effect of work boredom on cyberloafing behavior in millennial generation employees and to examine the effect of work stress as a mediating variable between job boredom and cyberloafing behavior in millennial employees. The analytical methods used are validity and reliability test, classical assumption test, simple linier regression test, path analysis, and sobel test. The number of samples in this study amounted to 125 millennial generation employees in Central Java. In this study, the object is determined by the following criteria: 1) an employee or office worker who works in Central Java 2) an employee born in 1980-2000 (millennial generation) 3) an employee who uses a smartphone while working. This study shows the results that work boredom have a positive effect on cyberloafing behavior in millennial generation employees, job stress fully mediates the effect of work boredom on cyberloafing behavior in millennial employees. Keywords: Work Boredom, Cyberloafing Behavior, Job Stress